Education Systems and Foreign Direct Investment : Does External Efficiency Matter? - Wendlassida Miningou, Elise; Tapsoba, Sampawende (Washington, D.C. : International Monetary Fund, 2017)
This paper examines the effect of the efficiency of the education system on Foreign Direct Investment (FDI). First, it focuses on the external efficiency and applies a frontier-based measure as a proxy of the ability of countries to optimally convert the average years of schooling into income for individuals. Second, it shows the relationship between the external efficiency of the education system and FDI inflows by applying GMM regression technique. The results show that the efficiency level varies across regions and countries and appears to be driven by higher education and secondary vocational education. Similarly to other studies in the literature, there is no significant relationship between the average years of schooling and FDI inflows. However, this study shows that the external efficiency of the education system is important for FDI inflows. Improving the external efficiency of the education system can play a role in attracting FDI especially in non-resource rich countries, nonlandloked countries and countries in the low and medium human development groups.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet